1995
DOI: 10.1111/j.1748-1716.1995.tb09915.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein loss and capillary protein permeability in dependent regions upon quiet standing

Abstract: Seven healthy males were exposed to quiet standing (15 min) after supine rest. Alterations in the total mass of plasma proteins were analysed from changes in plasma volume (PV; determination of control PV and subsequently of induced per cent PV changes using Hb/Hct) and protein concentration as revealed in arterial blood collected after standing. This approach adopted the concept that valid data on overall circulatory haemoconcentrations prevailing on standing can only be reached when blood is sampled on resum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…These various studies have shown that PV may shift from 10% up to 18% [11][12][13][14] in response to a person changing from a supine to an upright posture. Plasma volume shifts that may contribute to aberrant Hct values have been observed by many researchers using various techniques, including Evans blue dye, carbon monoxide dilution, and the mechanical oscillator technique.…”
Section: Discussionmentioning
confidence: 99%
“…These various studies have shown that PV may shift from 10% up to 18% [11][12][13][14] in response to a person changing from a supine to an upright posture. Plasma volume shifts that may contribute to aberrant Hct values have been observed by many researchers using various techniques, including Evans blue dye, carbon monoxide dilution, and the mechanical oscillator technique.…”
Section: Discussionmentioning
confidence: 99%
“…PV and glomerular filtration rate decrease [29]. In a recent study [30] as much as 20% of PV was sequestered in ESF within 15 min. There was a similar decrease in plasma albumin content (approximately 20%), but no decrease in larger proteins.…”
Section: Plasma Protein Circulationmentioning
confidence: 90%
“…Changing from supine to upright leads to an increase of both systemic haematocrit and plasma protein concentration (Thompson et al 1928;Hagan et al 1978;HinghoferSzalkay et al 1995;Bjerkhoel et al 1995). This means that below the location of hydrostatic indifference, where capillary pressures rise after assumption of an erect position, the extent of filtration out of the microvascular bed exceeds the inward fluid movement that, at the same time, occurs in capillaries above the hydrostatic indifference level.…”
Section: Capillary Filtrationmentioning
confidence: 93%